Habitat type and island identity as drivers of community assembly in an archipelago. (18th October 2020) - Chiarucci, Alessandro; Buldrini, Fabrizio; Cervellini, Marco; Guarino, Riccardo; Caccianiga, Marco; Foggi, Bruno; Viciani, Daniele; Lazzaro, Lorenzo; Casella, Laura; Angelini, Pierangela; Cerabolini, Bruno Enrico Leone; Pasta, Salvatore; et al.
Abstract: Aim: Ecoinformatics offer new opportunity to test islands as biogeographic and ecological models. In this paper we predicted three hypotheses: (1) plot‐based data issuing from vegetation surveys can be used to predict Island Species‐Area Relationships (ISARs) or island similarity; (2) the habitat area is an independent predictor of species richness patterns within island; (3) species richness and composition are more dependent on habitat type than island identity in land‐bridge islands. Area: Tuscan Archipelago, Italy. Methods: We assembled a database of all the vegetation plots available for the archipelago. For the first hypothesis we calculated ISARs, using Arrhenius model, and Beta Diversity, using Jaccard dissimilarity, on both published floras and cumulative plot data. For the second hypothesis, we modelled Habitat Species‐Area Relationships (HSARs), using Arrhenius model. For the third hypothesis, we used additive partitioning of species richness, NMDS and PERMANOVA. Results: Island Species‐Area Relationships based on plot data mirrored those on published floras, but absolute values of c and z parameters were different. Beta diversity based on plot data resembled those of published floras, but was higher. Species richness was significantly related to the habitat area. The total species richness of the archipelago was linked to large scale drivers, such as island identity, while plot species composition was driven by both habitat type and island identity. Conclusions: Data assembled issuing from vegetation surveys are useful to describe biogeographic patterns. Species richness in the archipelago is driven by spatial factors such as the amount of habitats and the differences among islands, while the species composition of local assemblages is largely driven by habitat filters rather than by island identity, as expected in land‐bridge islands. Abstract : We used a vegetation plot database to perform an island biogeography tests on the Tuscan Archipelago, showing the potential of such data to model Island Species–Area Relationships and beta diversity patterns. In such a land‐bridge system, species richness is driven by the number of habitats and differences among islands, while local species composition is driven by habitat filters rather than island identity.